The Toxicity of Lead and Lead‐Free Perovskite Precursors and Nanocrystals to Human Cells and Aquatic Organisms - Immacolata Maietta; Clara Otero‐Martínez; Sabela Fernández; Laura Sánchez; África González‐Fernández; Lakshminarayana Polavarapu; Rosana Simón‐Vázquez (Advanced Science)
Abstract Halide perovskites have emerged at the forefront of semiconductor materials for photovoltaic and light‐emitting devices. However, long‐term stability and toxicity are the major barriers to their commercialization. In particular, the toxicity of lead (Pb) and its environmental impact have prompted the exploration of lead‐free alternatives like tin (Sn) and bismuth (Bi). Herein, a cytotoxicity study of Pb‐based perovskite (CsPbBr3 and CsPbI3) and a lead‐free Cs2AgBiBr6 nanocrystals in lung and liver cell lines and in blood cells are reported, revealing that both Pb and Bi exhibit mitogenic effects and oxidative stress in liver cells, cytotoxicity in pulmonary cells and a dose‐dependent hemolytic effect, raising concerns about their potential pulmonary‐hepato‐hemotoxicity. The zebrafish embryo tests reveal SnBr2 displays a notably safer environmental impact profile at elevated concentrations, while Pb and Bi exhibit dose‐dependent toxicity. This study provides compelling evidence that Sn compounds demonstrate a safer toxicity profile in both human cells and aquatic organisms under the studied conditions, supporting their potential as a more environmentally friendly alternative. In contrast, Bi compounds exhibit a toxicity profile similar to Pb perovskites, warranting caution in its use as a substitute. These findings guide future research and regulatory efforts in the safety and sustainability of perovskite nanocrystals.